DEVELOPMENT OF THE PRINCIPLES OF FORMING THE STRUCTURE OF UNIVERSAL GEAR AND LEVER MECHANISMS - SMUTKO, SVITLANA; PIDHAICHUK, SVITLAN; ONOFRIICHUK, VOLODYMYR; ROMANETS, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2023)
There are wide possibilities of using gear-lever mechanisms in the transformation of uniform rotary motion of the driving link into reciprocating, oscillating, non-uniform rotary or movement along a complex closed trajectory.  The use of satellite curves of planetary mechanisms in combination with lever mechanisms allows to obtain a wide range of trajectories of executive bodies.But the use of satellite curves in the mechanisms of the working bodies of some technological machines, the dimensions of which movements lie within 5-30 mm, is connected with a number of limitations. Known mechanisms make it possible to obtain a movement of the executive bodies of at least 50 mm, reducing this limit leads to a decrease in the geometric parameters of gear planetary mechanisms, which leads to the impossibility of ensuring technological efforts, or to the complication of the lever part of gear-lever mechanisms. The development of planetary mechanisms, which will provide the required dimensions of the satellite curves, will allow the creation of gear-lever mechanisms, the trajectories of the movement of the executive organs of which will satisfy the laws of movement of the working organs of the required dimensions.In order to solve the problem of reducing the size of satellite curves, provided that technological efforts are ensured, it is necessary to look for fundamentally new constructive solutions of gear-lever mechanisms. At the same time, it is necessary to strive for simplicity and compactness of machines when transmitting motion in any direction without reducing the accuracy of transmission, which would contribute to the universalization of mechanisms and machines.The work presents the results of the analysis of research methods and existing developments in the design of gear-lever mechanisms, their features are established, which allowed to determine the principles of the formation of structures of universal gear-lever mechanisms for driving the working bodies of technological machines.
Keywords: working bodies of technological machines; satellite curve; gear-lever mechanisms